Experiencia del usuario en plataformas de noticias digitales (El Diario De Riobamba) en Riobamba, período enero – junio 2023. - Moreno Uquillas, Itati Micaela (2025)
The purpose of this research was to interpret user preferences in the consumption of visual content on Diario de Riobamba platforms with a vision of digital communication and communication. The methodology used was focused on the interpretive paradigm, phenomenological method, design, and descriptive-interpretive. Interviews were conducted with three experts in communication and digital communication to provide relevant information from the perspectives of professionals. To systematize and compare their responses, a coincidence matrix was created that includes five key categories of analysis. For the content analysis, the focus was on the review of the publications on the platforms of the Diario de Riobamba from January to June 2023. The combination of the experiences of the users on the different platforms of the medium was used to identify the main visual content that users prefer and what impact it has had. The emerging findings show that users especially value relevant content, prioritizing the quality and accessibility of visual content in order also to enhance loyalty among their followers and reach a broader audience.